Applications of Stem Cells in Veterinary Medicine - Masharing, N; Kumar, Suresh; Mahanta, N; Dewry, R K; Kalita, Manoj K.; Kumar, Ashok (Indian Journal of Hill Farming, 2018)
The stem cell field in veterinary medicine continues to evolve rapidly both experimentally and clinically. Stem cells are most commonly used in clinical veterinary medicine in therapeutic applications for the treatment of musculoskeletal injuries. New technologies of assisted reproduction are being developed to apply the properties of spermatogonial stem cells to preserve endangered animal species which can also be used to generate transgenic animals for production of pharmaceuticals or for use as biomedical models. Small and large animals serve as valuable models for preclinical evaluation of stem cell applications in human beings and in veterinary, in areas such as spinal cord injury and myocardial infarction. Reviews on the use of animal models for stem cell research have been published recently. Therefore, in this overview, animal model research will be reviewed only in the context of supporting the current clinical application of stem cells especially in veterinary medicine.